Multi-scale finite element simulation of needle-punched quartz fiber reinforced composites - Niu Weijing; Yan Xiaopeng; Shi Haolin; Guo Zhangxin (Science and Engineering of Composite Materials)
To investigate the effects of different needling parameters on the mechanical properties of quartz needled felts and their composites, this paper proposes a multi-scale modeling approach to simulate and calculate the mechanical properties of needled quartz fiber-reinforced composites. Firstly, based on the characteristics of needle-punching technology, the morphology of needle-punched composites was analyzed at a microscopic scale, and the quartz fiber structure was divided into three typical representative regions. Then, a periodic single-cell model of needled composites was established. Meanwhile, this article also analyzes the influence of parameters such as needling density, needle type, and needling depth on the mechanical properties of needled composites.